Treatment method for enhancing strength of alumina ceramic

By adding zirconium dioxide powder and silicon carbide fibers to alumina ceramics, combined with cold isostatic molding and hot isostatic pressure treatment, and finally using laser surface treatment, the problem of insufficient brittleness and toughness of alumina ceramic materials is solved, significantly improving its strength and toughness, and expanding its application range.

CN119684019APending Publication Date: 2025-03-25NANTONG BOCHUANG FINE CERAMIC CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411902481.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Alumina ceramic materials limit their application in high stress environments due to their inherent brittleness and low fracture toughness.

Method used

By adding reinforcement materials to the alumina powder, including zirconium dioxide powder and silicon carbide fibers, and combining cold isostatic molding technology and hot isostatic treatment, the strength and toughness of alumina ceramics are improved through laser surface treatment technology.

Benefits of technology

The strength and toughness of alumina ceramics are significantly improved, their application capabilities in high stress environments, and their mechanical properties are further enhanced through improved microstructure and surface treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684019A_ABST
    Figure CN119684019A_ABST
Patent Text Reader

Abstract

The invention discloses a treatment method for enhancing the strength of aluminum oxide ceramics in the technical field of aluminum oxide ceramics. The treatment method comprises the following steps: S1, selecting an enhancing material; s2, mixing the base material and the reinforcing material; s3, carrying out pressure forming on the mixed material; s4, sintering the aluminum oxide ceramic model; s5, performing hot isostatic pressing treatment on the aluminum oxide ceramic sample; s6, laser surface treatment; by improving the formula of the aluminum oxide ceramic and adding a reinforcing material into the aluminum oxide powder, the strength of the aluminum oxide ceramic can be improved, the strength and toughness of the aluminum oxide ceramic are improved by the zirconium dioxide powder, the strength and toughness of the aluminum oxide ceramic are improved by the silicon carbide fiber, and then the density gradient is reduced by matching multiple processing modes; the porosity is reduced, the density is increased, pores in the aluminum oxide ceramic are formed, the surface microstructure of the ceramic is changed, a pressure stress field is introduced, and the strength is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alumina ceramics, and in particular to a processing method for enhancing the strength of alumina ceramics. Background Art

[0002] Alumina ceramics are a type of ceramic material with aluminum oxide as the main component, used in thick film integrated circuits. Alumina ceramics have good conductivity, mechanical strength and high temperature resistance. It should be noted that ultrasonic cleaning is required. Alumina ceramics are a widely used ceramic. Due to their superior performance, they are increasingly widely used in modern society to meet the needs of daily use and special performance.

[0003] Alumina ceramics are the most common advanced precision ceramic materials and are also relatively traditional materials. High-purity alumina ceramics have been widely used in many industries as an excellent ceramic material. This material has excellent properties in electrical insulation, high thermal conductivity, high chemical resistance, good wear resistance and low thermal expansion.

[0004] Alumina ceramics are widely used in machinery, electronics, chemical industry and other industries due to their excellent hardness, wear resistance, corrosion resistance and good electrical insulation properties, especially in high temperature and high pressure environments. Although alumina ceramics have many advantages, their inherent brittleness and low fracture toughness limit their application in some high stress environments. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a processing method for enhancing the strength of alumina ceramics.

[0006] The object of the present invention is achieved by: a method for strengthening the strength of alumina ceramics, comprising the following steps: S1. Select reinforcing material: The reinforcing material is a mixture of multiple materials, and the reinforcing material includes zirconium dioxide powder and silicon carbide fiber. The reinforcing material is added to the alumina powder in proportion to obtain a mixed material; S2. Mixing the base material and the reinforcing material: fully stirring and mixing the mixed material by a ball milling mechanism, so that the reinforcing material and the alumina powder are fully mixed together to obtain a mixed material; S3, mixed material pressure molding: the mixed material is loaded into a mold, and the mixed material is pressure molded by cold isostatic pressing technology to obtain an alumina ceramic model; S4, sintering the alumina ceramic model: sintering the alumina ceramic model at a high temperature, and controlling the sintering temperature at 1700° C.-1900° C. and the sintering time at 4-12 h to obtain an alumina ceramic sample; S5. Hot isostatic pressing of the alumina ceramic sample: placing the sintered alumina ceramic sample into a hot isostatic pressing furnace, and processing the sample under high temperature of 1550°C-1770°C and high pressure of 111MPa-223MPa to obtain a finished alumina ceramic product; S6. Laser surface treatment: Use laser equipment to locally heat the surface of the finished alumina ceramic product, and change the surface microstructure of the finished alumina ceramic product through laser scanning to obtain an enhanced finished alumina ceramic product.

[0007] Specifically, the ratio of the reinforcing material to the alumina powder in the S1 is 91:9 to 95:5, the content of the alumina powder is 91%-95%, and the content of the reinforcing material is 9%-5%; the ratio of the zirconium dioxide powder to the silicon carbide fiber in the reinforcing material is 96:4 to 98:2, the content of the zirconium dioxide powder is 96%-98%, and the content of the silicon carbide fiber is 4%-2%.

[0008] Specifically, the reinforcing material and alumina powder in S1 are prepared by a sol-gel method, wherein zirconium dioxide, silicon carbide and alumina are first reacted by a sol to obtain a sol solution, and then the sol solution is further polymerized to generate a gel, and then the gel is dried to obtain an anhydrous solid, and then the anhydrous solid is heated and crystallized to finally obtain zirconium dioxide powder, alumina powder and silicon carbide fiber.

[0009] Specifically, the ball mill in S2 uses stainless steel balls as the milling medium, and the size of the ball milling medium is 10 mm, and the ball milling ratio of the ball mill is 1:5, and the rotation speed of the ball mill is between 50% and 70% of the critical rotation speed of the ball mill, and the capacity invested in the ball mill is 50% to 75% of the maximum capacity of the ball mill.

[0010] Specifically, during the process of mixing and stirring the reinforcing material and the alumina powder in the ball mill, larger particles are filtered out through a sieve before the reinforcing material and the alumina powder are put into the ball mill, and the reinforcing material and the alumina powder are dried. Then, the reinforcing material and the alumina powder are put into the ball mill, and a dispersant, a binder or a surfactant is added to the reinforcing material and the alumina powder, and the mixture is mixed and stirred for 0.5h-2h in the ball mill.

[0011] Specifically, the steps of the cold isostatic pressing technology in S3 are as follows: Prepare materials: put the mixed materials into the mold, the mixed materials are in fine granular form; Filling liquid: Fill the mold completely with liquid medium, which can be water, oil or special liquid, and ensure that the liquid evenly surrounds the mixed material; Applying pressure: isostatic pressure is applied to the mold through a pressurizing device, and the pressure is uniform in all directions of the mold, with a pressure range of 1000MPa-5000MPa; Solidification molding: Under the action of external pressure, the mixed materials are compacted with each other to achieve the desired density and shape to obtain an alumina ceramic model.

[0012] Specifically, the high temperature sintering in S4 adopts a sealed sintering furnace. When sintering, a protective gas is first filled into the sintering furnace, and the protective gas is oxygen or argon, and then a pre-sintering treatment is performed, that is, heating at a temperature of 600°C-1000°C and maintaining it for 1-2h; After high-temperature sintering, the alumina ceramic sample is slowly cooled to room temperature, and the sintered alumina ceramic sample is surface treated to remove excess material on the surface of the alumina ceramic sample. Then, a scanning electron microscope is used to perform microstructural analysis on the surface of the alumina ceramic sample.

[0013] Specifically, the steps of hot isostatic pressing in S5 are as follows: Heating and pressurizing: Place the alumina ceramic sample in a hot isostatic pressing furnace and heat it to 1550℃-1770℃. During the heating process, isostatic pressure is applied at the same time. The isostatic pressure is controlled between 111MPa-223MPa. Holding stage: After heating to the specified temperature, keep it at high temperature and high pressure for 5-10 hours; Cooling: After the holding time is reached, slowly cool down, that is, control the temperature in the hot isostatic pressing furnace, and control the temperature to drop by 10°C every 0.5h until the temperature in the isostatic pressing furnace is the same as the room temperature. After the temperature in the isostatic pressing furnace cools to room temperature, keep it for another 2h, and then gradually release the external pressure to restore the alumina ceramic sample to normal; Surface inspection: The surface of the alumina ceramic sample was then subjected to microstructural analysis using a scanning electron microscope.

[0014] Specifically, before the hot isostatic pressing furnace is heated and heated, the air in the hot isostatic pressing furnace is extracted to maintain a vacuum environment inside the hot isostatic pressing furnace, or an inert gas is filled into the hot isostatic pressing furnace and the air inside the hot isostatic pressing furnace is discharged so that the hot isostatic pressing furnace is filled with an inert gas, and the inert gas used is helium, neon, argon or krypton.

[0015] Specifically, the processing steps of the laser device in S6 are as follows: Clean the surface of the finished alumina ceramic product to remove impurities and oil stains; Preheating the surface of the finished alumina ceramic product; Use laser equipment to locally heat the surface of the finished alumina ceramic product, and change the microstructure of the surface of the finished alumina ceramic product through laser scanning; After laser treatment, the surface of the finished alumina ceramic product is cooled by natural cooling or forced cooling. After the laser surface treatment, the finished alumina ceramic product is tempered, and the surface of the finished alumina ceramic product is polished and ground.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention effectively improves the strength of alumina ceramics by adding reinforcing materials to alumina powder, and the reinforcing materials include zirconium dioxide powder and silicon carbide fibers. The zirconium dioxide powder is added to the alumina powder to improve the strength and toughness of the alumina ceramics. The doped oxide forms a uniformly distributed reinforcement phase in the alumina matrix, thereby improving the mechanical properties of the ceramics. In addition, the addition of silicon carbide fibers to alumina can significantly improve the strength and toughness of the alumina ceramics. The silicon carbide fibers play a role in dispersing stress in the ceramics and reducing the expansion of cracks. The strength of alumina ceramics is improved by combining cold isostatic pressing technology with hot isostatic pressing. Cold isostatic pressing technology applies uniform liquid pressure to compact powders, avoiding the density gradient in traditional pressing methods. It also optimizes the microstructure of alumina ceramics, reduces porosity, increases density, and significantly improves the strength and hardness of alumina ceramics by controlling parameters such as sintering temperature and sintering atmosphere. Hot isostatic pressing is then used to promote the densification of alumina, reduce the pores inside alumina ceramics, and further improve the strength. Finally, the surface of the finished alumina ceramics is treated by laser equipment. Laser surface treatment technology can improve its crack resistance by changing the microstructure of the ceramic surface and introducing a compressive stress field. In summary, by improving the formula of alumina ceramics and adding reinforcing materials to alumina powder, the strength of alumina ceramics themselves can be improved. Then, through the coordination of various processing methods, the density gradient can be reduced, the porosity can be reduced, the density can be increased, the pores inside the alumina ceramics can be reduced, the microstructure of the ceramic surface can be changed, and a compressive stress field can be introduced to further improve the strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0018] Figure 1It is a schematic diagram of the steps of the present invention; Figure 2 It is a schematic diagram of the steps of the cold isostatic pressing technology of the present invention; Figure 3 It is a schematic flow chart of the steps of hot isostatic pressing treatment of the present invention; Figure 4 It is a schematic flow chart of the processing steps of the laser device of the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] like Figure 1-4 A method for enhancing the strength of alumina ceramics is shown, comprising the following steps: S1. Select reinforcing material: The reinforcing material is a mixture of multiple materials, and the reinforcing material includes zirconium dioxide powder and silicon carbide fiber. The reinforcing material is added to the alumina powder in proportion to obtain a mixed material; S2. Mixing the base material and the reinforcing material: fully stirring and mixing the mixed material by a ball milling mechanism, so that the reinforcing material and the alumina powder are fully mixed together to obtain a mixed material; S3, mixed material pressure molding: the mixed material is loaded into a mold, and the mixed material is pressure molded by cold isostatic pressing technology to obtain an alumina ceramic model; S4, sintering the alumina ceramic model: sintering the alumina ceramic model at a high temperature, and controlling the sintering temperature at 1700° C.-1900° C. and the sintering time at 4-12 h to obtain an alumina ceramic sample; S5. Hot isostatic pressing of the alumina ceramic sample: placing the sintered alumina ceramic sample into a hot isostatic pressing furnace, and processing the sample under high temperature of 1550°C-1770°C and high pressure of 111MPa-223MPa to obtain a finished alumina ceramic product; S6. Laser surface treatment: Use laser equipment to locally heat the surface of the finished alumina ceramic product, and change the surface microstructure of the finished alumina ceramic product through laser scanning to obtain an enhanced finished alumina ceramic product.

[0021] In this embodiment, preferably, the ratio of the reinforcing material to the alumina powder in S1 is 91:9 to 95:5, the content of the alumina powder is 91%-95%, and the content of the reinforcing material is 9%-5%; the ratio of the zirconium dioxide powder to the silicon carbide fiber in the reinforcing material is 96:4 to 98:2, the content of the zirconium dioxide powder is 96%-98%, and the content of the silicon carbide fiber is 4%-2%; It should be noted that the mixing ratio of alumina powder and reinforcing materials will vary according to different target performance, types of doping materials and required microstructures. The addition of reinforcing materials can enhance the toughness, hardness and thermal shock resistance of alumina. The addition of zirconium can improve the crack resistance of alumina through "particle strengthening" or "phase change hardening", especially improve the thermal shock resistance of the material. The addition of silicon carbide fibers can significantly improve its strength and toughness, play a role in dispersing stress and reducing crack expansion.

[0022] In this embodiment, preferably, the reinforcing material and the alumina powder in S1 are prepared by a sol-gel method, firstly, zirconium dioxide, silicon carbide and alumina are reacted by a sol to obtain a sol solution, and then the sol solution is further polymerized to generate a gel, and then the gel is dried to obtain an anhydrous solid, and then the anhydrous solid is heated and crystallized to finally obtain zirconium dioxide powder, alumina powder and silicon carbide fiber; It should be noted that the preparation of composite materials by the sol-gel method can effectively control their microstructure and enhance the performance of alumina ceramics. The sol-gel method can accurately control the grain size, phase composition and morphology of the material, so that the prepared powder and fiber have better mechanical properties and thermal stability.

[0023] In this embodiment, preferably, the ball mill in S2 uses stainless steel ball as the ball milling medium, and the size of the ball milling medium is 10 mm, and the ball milling ratio of the ball mill is 1:5, and the speed of the ball mill is between 50% and 70% of the critical speed of the ball mill, and the capacity invested in the ball mill is 50% to 75% of the maximum capacity of the ball mill; It should be noted that the ball milling media of stainless steel balls can reduce the reaction with the reinforcing material and alumina powder, and the size of the ball milling media and the setting of the ball milling ratio can improve the mixing effect of the reinforcing material and alumina powder and improve the mixing degree. The rotation speed of the ball mill may cause excessive jumping of the grinding balls and reduce the mixing effect of the powder; too low a rotation speed may cause uneven mixing of the powder, and adding the capacity in the ball mill to two-thirds can reduce the splashing of the reinforcing material and alumina powder.

[0024] In this embodiment, preferably, during the process of mixing and stirring the reinforcing material and the alumina powder in the ball mill, before the reinforcing material and the alumina powder are put into the ball mill, the larger particles are first filtered out through a screen, and the reinforcing material and the alumina powder are dried, and then the reinforcing material and the alumina powder are put into the ball mill, and then a dispersant, a binder or a surfactant is added to the reinforcing material and the alumina powder, and the reinforcing material and the alumina powder are mixed and stirred for 0.5h-2h by the ball mill; It should be noted that screening can ensure that the particle size of the material entering the ball mill is relatively uniform, which helps to obtain a more uniform mixing and refining effect during the ball milling process. Drying can ensure that the reinforcing material and alumina powder are more stable during subsequent processing and avoid adhesion or uneven mixing in a wet state. The purpose of adding dispersants, binders or surfactants is to improve the mixing effect of the materials and the dispersibility of the particles.

[0025] In this embodiment, preferably, the steps of the cold isostatic pressing technology in S3 are as follows: Prepare materials: put the mixed materials into the mold, the mixed materials are in fine granular form; Filling liquid: Fill the mold completely with liquid medium, which can be water, oil or special liquid, and ensure that the liquid evenly surrounds the mixed material; Applying pressure: isostatic pressure is applied to the mold through a pressurizing device, and the pressure is uniform in all directions of the mold, with a pressure range of 1000MPa-5000MPa; Solidification molding: Under the action of external pressure, the mixed materials are compacted to achieve the desired density and shape to obtain an alumina ceramic model; It should be noted that the cold isostatic pressing technology allows the mixed material to be subjected to uniform pressure in all directions, thereby achieving very uniform density and mechanical properties, and avoiding the density gradient in traditional pressing methods.

[0026] In this embodiment, preferably, the high temperature sintering in S4 adopts a sealed sintering furnace. When sintering, a protective gas is first filled into the sintering furnace, and the protective gas is oxygen or argon, and then a pre-sintering treatment is performed, that is, heating at a temperature of 600°C-1000°C and maintaining it for 1-2h; After high-temperature sintering, the alumina ceramic sample is slowly cooled to room temperature, and the sintered alumina ceramic sample is surface treated to remove excess material on the surface of the alumina ceramic sample, and then a scanning electron microscope is used to perform microstructural analysis on the surface of the alumina ceramic sample; It should be noted that by filling a sealed sintering furnace with protective gas, the alumina ceramic samples can be prevented from being affected by the oxidation reaction during sintering, and the surface of the alumina ceramic samples is treated after cooling to improve the integrity and smoothness of the surface of the alumina ceramic samples. The surface of the alumina ceramic samples is microstructured and analyzed to check for unqualified products.

[0027] In this embodiment, preferably, the steps of hot isostatic pressing in S5 are as follows: Heating and pressurizing: Place the alumina ceramic sample in a hot isostatic pressing furnace and heat it to 1550℃-1770℃. During the heating process, isostatic pressure is applied at the same time. The isostatic pressure is controlled between 111MPa-223MPa. Holding stage: After heating to the specified temperature, keep it at high temperature and high pressure for 5-10 hours; Cooling: After the holding time is reached, slowly cool down, that is, control the temperature in the hot isostatic pressing furnace, and control the temperature to drop by 10°C every 0.5h until the temperature in the isostatic pressing furnace is the same as the room temperature. After the temperature in the isostatic pressing furnace cools to room temperature, keep it for another 2h, and then gradually release the external pressure to restore the alumina ceramic sample to normal; Surface inspection: Scanning electron microscope equipment is then used to perform microstructural analysis on the surface of the alumina ceramic sample; It should be noted that hot isostatic pressing can effectively eliminate porosity, increase density, and improve mechanical properties by treating materials under high temperature and high pressure conditions. The thermal conductivity, thermal fatigue resistance and other properties of the material are also improved. Due to the reduction in porosity, the mechanical properties of the material (such as strength, fatigue performance, corrosion resistance, etc.) are greatly improved, especially the working performance under high temperature or high pressure conditions, which significantly reduces failures caused by porosity and improves the yield in the production process.

[0028] In this embodiment, preferably, before the hot isostatic pressing furnace is heated and heated, the air in the hot isostatic pressing furnace is extracted to maintain the inside of the hot isostatic pressing furnace in a vacuum environment, or an inert gas is filled into the hot isostatic pressing furnace and the air in the hot isostatic pressing furnace is discharged so that the inside of the hot isostatic pressing furnace is filled with inert gas, and the inert gas used is helium, neon, argon or krypton; It should be noted that the air in the hot isostatic pressing furnace is discharged to maintain the vacuum and inert gas inside the hot isostatic pressing furnace, which can reduce the impact of oxidation reaction when the hot isostatic pressing furnace is processing alumina ceramic products.

[0029] In this embodiment, preferably, the processing steps of the laser device in S6 are as follows: Clean the surface of the finished alumina ceramic product to remove impurities and oil stains; Preheating the surface of the finished alumina ceramic product; Use laser equipment to locally heat the surface of the finished alumina ceramic product, and change the microstructure of the surface of the finished alumina ceramic product through laser scanning; After laser treatment, the surface of the finished alumina ceramic product is cooled by natural cooling or forced cooling. After the laser surface treatment, the finished alumina ceramic product is tempered, and the surface of the finished alumina ceramic product is polished and ground; It should be noted that laser surface treatment technology has the advantages of high precision, high efficiency, and low thermal impact. It uses a high-power laser beam to locally heat and modify the surface of the material. It can improve its crack resistance by changing the microstructure of the ceramic surface and introducing a compressive stress field.

[0030] The specific operation process of this application: Step 1: Select reinforcing material: The reinforcing material is a mixture of multiple materials, and the reinforcing material includes zirconium dioxide powder and silicon carbide fiber. The reinforcing material is added to the alumina powder in proportion to obtain a mixed material; Step 2: Mixing the base material and the reinforcing material: Fully stirring and mixing the mixed material by a ball mill mechanism, so that the reinforcing material and the alumina powder are fully mixed together to obtain a mixed material; Step 3: Pressing and molding the mixed material: loading the mixed material into a mold, and pressurizing the mixed material by cold isostatic pressing technology to obtain an alumina ceramic model; Step 4: Sintering the alumina ceramic model: Sintering the alumina ceramic model at a high temperature, and controlling the sintering temperature at 1700° C.-1900° C. and the sintering time at 4-12 h to obtain an alumina ceramic sample; Step 5, hot isostatic pressing the alumina ceramic sample: placing the sintered alumina ceramic sample into a hot isostatic pressing furnace, and processing it under high temperature of 1550°C-1770°C and high pressure of 111MPa-223MPa to obtain an alumina ceramic finished product; Step 6. Laser surface treatment: Use laser equipment to locally heat the surface of the finished alumina ceramic product, and change the surface microstructure of the finished alumina ceramic product through laser scanning to obtain an enhanced finished alumina ceramic product.

[0031] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for enhancing the strength of alumina ceramics: characterized in that: The following steps are involved: S1. Select reinforcing material: The reinforcing material is a mixture of multiple materials, and the reinforcing material includes zirconium dioxide powder and silicon carbide fiber. The reinforcing material is added to the alumina powder in proportion to obtain a mixed material; S2. Mixing the base material and the reinforcing material: fully stirring and mixing the mixed material by a ball milling mechanism, so that the reinforcing material and the alumina powder are fully mixed together to obtain a mixed material; S3, mixed material pressure molding: the mixed material is loaded into a mold, and the mixed material is pressure molded by cold isostatic pressing technology to obtain an alumina ceramic model; S4, sintering the alumina ceramic model: sintering the alumina ceramic model at a high temperature, and controlling the sintering temperature at 1700° C.-1900° C. and the sintering time at 4-12 h to obtain an alumina ceramic sample; S5. Hot isostatic pressing of the alumina ceramic sample: placing the sintered alumina ceramic sample into a hot isostatic pressing furnace, and processing the sample under high temperature of 1550°C-1770°C and high pressure of 111MPa-223MPa to obtain a finished alumina ceramic product; S6. Laser surface treatment: Use laser equipment to locally heat the surface of the finished alumina ceramic product, and change the surface microstructure of the finished alumina ceramic product through laser scanning to obtain an enhanced finished alumina ceramic product.

2. A method for enhancing the strength of alumina ceramics according to claim 1, characterized in that: The ratio of the reinforcing material to the alumina powder in the S1 is 91:9 to 95:5, the content of the alumina powder is 91%-95%, and the content of the reinforcing material is 9%-5%; the ratio of the zirconium dioxide powder to the silicon carbide fiber in the reinforcing material is 96:4 to 98:2, the content of the zirconium dioxide powder is 96%-98%, and the content of the silicon carbide fiber is 4%-2%.

3. A method for enhancing the strength of alumina ceramics according to claim 1, characterized in that: The reinforcing material and alumina powder in S1 are prepared by a sol-gel method, wherein zirconium dioxide, silicon carbide and alumina are first reacted by a sol to obtain a sol solution, and then the sol solution is polymerized to generate a gel, and then the gel is dried to obtain an anhydrous solid, and then the anhydrous solid is heated and crystallized to finally obtain zirconium dioxide powder, alumina powder and silicon carbide fiber.

4. The method for enhancing the strength of alumina ceramics according to claim 1, characterized in that: The ball mill in S2 uses stainless steel balls as the milling medium, and the size of the ball mill is 10 mm. The milling ratio of the ball mill is 1:5, and the rotation speed of the ball mill is between 50% and 70% of the critical rotation speed of the ball mill. The capacity invested in the ball mill is 50% to 75% of the maximum capacity of the ball mill.

5. A method for enhancing the strength of alumina ceramics according to claim 4, characterized in that: During the process of mixing and stirring the reinforcing material and the alumina powder in the ball mill, larger particles are filtered out through a sieve before the reinforcing material and the alumina powder are put into the ball mill, and the reinforcing material and the alumina powder are dried. Then the reinforcing material and the alumina powder are put into the ball mill, and a dispersant, a binder or a surfactant is added to the reinforcing material and the alumina powder, and the mixture is mixed and stirred for 0.5h-2h in the ball mill.

6. The method for enhancing the strength of alumina ceramics according to claim 1, characterized in that: The steps of the S3 cold isostatic pressing technology are as follows: Prepare materials: put the mixed materials into the mold, the mixed materials are in fine granular form; Filling liquid: Fill the mold completely with liquid medium, which can be water, oil or special liquid, and ensure that the liquid evenly surrounds the mixed material; Applying pressure: isostatic pressure is applied to the mold through a pressurizing device, and the pressure is uniform in all directions of the mold, with a pressure range of 1000MPa-5000MPa; Solidification molding: Under the action of external pressure, the mixed materials are compacted with each other to achieve the desired density and shape to obtain an alumina ceramic model.

7. The method for enhancing the strength of alumina ceramics according to claim 1, characterized in that: The high temperature sintering in S4 adopts a sealed sintering furnace. When sintering, a protective gas is first filled into the sintering furnace, and the protective gas is oxygen or argon, and then a pre-sintering treatment is performed, that is, heating at a temperature of 600°C-1000°C and maintaining it for 1-2h; After high-temperature sintering, the alumina ceramic sample is slowly cooled to room temperature, and the sintered alumina ceramic sample is surface treated to remove excess material on the surface of the alumina ceramic sample. Then, a scanning electron microscope is used to perform microstructural analysis on the surface of the alumina ceramic sample.

8. The method for enhancing the strength of alumina ceramics according to claim 1, characterized in that: The steps of the hot isostatic pressing treatment in S5 are as follows: Heating and pressurizing: Place the alumina ceramic sample in a hot isostatic pressing furnace and heat it to 1550℃-1770℃. During the heating process, isostatic pressure is applied at the same time. The isostatic pressure is controlled between 111MPa-223MPa. Holding stage: After heating to the specified temperature, keep it at high temperature and high pressure for 5-10 hours; Cooling: After the holding time is reached, slowly cool down, that is, control the temperature in the hot isostatic pressing furnace, and control the temperature to drop by 10°C every 0.5h until the temperature in the isostatic pressing furnace is the same as the room temperature. After the temperature in the isostatic pressing furnace cools to room temperature, keep it for another 2h, and then gradually release the external pressure to restore the alumina ceramic sample to normal; Surface inspection: The surface of the alumina ceramic sample was then subjected to microstructural analysis using a scanning electron microscope.

9. A method for enhancing the strength of alumina ceramics according to claim 8, characterized in that: Before the hot isostatic pressing furnace is heated and heated, the air in the hot isostatic pressing furnace is extracted to maintain the interior of the hot isostatic pressing furnace in a vacuum environment, or an inert gas is filled into the hot isostatic pressing furnace and the air in the hot isostatic pressing furnace is discharged so that the interior of the hot isostatic pressing furnace is filled with an inert gas, and the inert gas used is helium, neon, argon or krypton.

10. The method for strengthening alumina ceramics according to claim 1, characterized in that: The processing steps of the laser device in S6 are as follows: Clean the surface of the finished alumina ceramic product to remove impurities and oil stains; Preheating the surface of the finished alumina ceramic product; Use laser equipment to locally heat the surface of the finished alumina ceramic product, and change the microstructure of the surface of the finished alumina ceramic product through laser scanning; After laser treatment, the surface of the finished alumina ceramic product is cooled by natural cooling or forced cooling. After the laser surface treatment, the finished alumina ceramic product is tempered, and the surface of the finished alumina ceramic product is polished and ground.

Citation Information

Patent Citations

  • Rare-earth alumina ceramic composite material and preparation method thereof

    CN108083779A

  • Alumina ceramic, preparation method thereof and ceramic bearing

    CN111302777A

  • Preparation method of nano-zirconia toughened nano-alumina ceramic

    CN117383914A

  • Ceramic lens and method of increasing ceramic luminousness

    CN1834695A

  • Method of making composite articles containing a ceramic matrix reinforced by zirconia particles and optionally by monocrystalline silicon carbide fibres, and articles obtained thereby

    EP0263033A2